2018
DOI: 10.7759/cureus.2689
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Posterior Interosseous Nerve Lipoma with Complete Paralysis: Case Report and Review of the Literature

Abstract: An intraneural posterior interosseous nerve (PIN) lipoma is a rare entity consisting of two types and only two previously reported cases. Treatment involves total excision for the well-encapsulated “true intraneural lipomas” type and subtotal resection for the other type, fibrolipomatous hamartomas of the nerve. We present the management and surgical treatment of a case that illustrates a variation of the traditional posterolateral surgical approach for the complete excision of an intraneural PIN lipoma—contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(24 reference statements)
0
7
0
1
Order By: Relevance
“…After duplicates were consolidated and articles screened for relevancy, 30 articles comprising 34 patients met inclusion criteria and were included in the analysis (Supplementary Table 1). 3,5-35 Studies comprised of case series and reports dating from 1953 to 2019. Each study included 1 to 4 patients, 31 of which described 1 patient.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were consolidated and articles screened for relevancy, 30 articles comprising 34 patients met inclusion criteria and were included in the analysis (Supplementary Table 1). 3,5-35 Studies comprised of case series and reports dating from 1953 to 2019. Each study included 1 to 4 patients, 31 of which described 1 patient.…”
Section: Resultsmentioning
confidence: 99%
“…There are several case reports of proximal radio-ulnar ganglion lesions involving the PIN with excellent recovery following excision [9], of intraneural PIN lipomas [10], isolated case reports of PIN schwannomas [11], neuralgic amyotrophy presenting as an isolated PIN palsy [12], and rheumatoid arthritis with synovial invasion [13].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal surgical approach can vary depending on the lipoma's anatomical relation and the distribution of the adjacent peripheral nerves (10). Patel AP et al reported that the anterior approach is the most frequent, and it is shown to have better outcomes (10). Therefore, the anterior surgical approach was performed through the forearm's flexor compartment between the brachioradialis and brachialis muscles in order to achieve optimal recovery and save the branches of the adjacent peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%